Nasal high flow therapy: a novel treatment rather than a more expensive oxygen device. (8th September 2017) - Ischaki, Eleni; Pantazopoulos, Ioannis; Zakynthinos, Spyros
Nasal high flow is a promising novel oxygen delivery device, whose mechanisms of action offer some beneficial effects over conventional oxygen systems. The administration of a high flow of heated and humidified gas mixture promotes higher and more stable inspiratory oxygen fraction values, decreases anatomical dead space and generates a positive airway pressure that can reduce the work of breathing and enhance patient comfort and tolerance. Nasal high flow has been used as a prophylactic tool or as a treatment device mostly in patients with acute hypoxaemic respiratory failure, with the majority of studies showing positive results. Recently, its clinical indications have been expanded to post-extubated patients in intensive care or following surgery, for pre- and peri-oxygenation during intubation, during bronchoscopy, in immunocompromised patients and in patients with "do not intubate" status. In the present review, we differentiate studies that suggest an advantage (benefit) from other studies that do not suggest an advantage (no benefit) compared to conventional oxygen devices or noninvasive ventilation, and propose an algorithm in cases of nasal high flow application in patients with acute hypoxaemic respiratory failure of almost any cause. Most studies favour NHF over conventional oxygen therapy, but it is unknown which patients will benefit the most http://ow.ly/Dmk830cBTKY